Calcareous nannofossil assemblages and their significance in defining the of the Jurassic/Cretaceous boundary - Concheyro, Graciela (2021)
In the latest Jurassic a major speciation episode for calcareous nannofossils took place with the appearance and rapid evolution of several new genera and species. In this contribution, we analyzed the calcareous nannofossil biostratigraphy around the Jurassic/Cretaceous boundary of sections from different latitudes and paleogeographic settings. From south to north, they were the Neuquén Basin, Argentina, Sierra Madre Oriental, Mexico, and Feodosiya, Crimea. The Tithonian? Berriasian interval in the Neuquén Basin, Argentina, was represented by marine shales and limestones of the Vaca Muerta Formation deposited as a result of a rapid and generalized paleo-Pacific marine transgression. In Mexico, at the Sierra Madre Oriental, during the Tithonian to Berriasian, the development of shallow marine environment occurred, characterized by sediments of the Pimienta Formation (carbonates) and Tamaulipas Formation (argillaceous limestones, shales), respectively. In Crimea, the upper Tithonian to the lower Berriasian was represented by sediments of the Dvuyakornaya Formation, Feodosiya region, characterized by calciturbidites, debrites, and pelagic deposits from the deeper part of a distally steepened ramp. In these localities five nannofossil bio-events indicated high reliability (First Occurrences of Polycostella beckmannii, Helenea chiastia, Nannoconus wintereri, Nannoconus kamptneri minor and Nannoconus steinmannii steinmannii), and four of them indicated moderate confidence (Fist Occurences of Hexalithus noeliae, Hexalithus geometricus, Cruciellipsis cuvillieri and the Last Occurrence of P. beckmannii) determining five biozones (NJT 15, NJT 16, NJT 17, NC0, and NC1). In the three sedimentary basins, the First Occurrences of N. wintereri and N. kamptneri minor were the most confident bioevents to approximate the Jurassic/Cretaceous boundary, and they correlated the Andean with middle latitude regions, improving our knowledge about the marine connections established between the southeastern Pacific and the Tethyan Realm during those times.